2018
DOI: 10.24251/hicss.2018.497
|View full text |Cite
|
Sign up to set email alerts
|

Says Who?: How News Presentation Format Influences Perceived Believability and the Engagement Level of Social Media Users

Abstract: We investigate whether the news presentation format affects the believability of a news story and the engagement level of social media users. Specifically, we test to see if highlighting the source delivering the story can nudge the users to think more critically about the truthfulness of the story that they see, and for obscure sources, whether source ratings can affect how the users evaluate the truthfulness. We also test whether the believability can influence the users' engagement level for the presented n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…In their study to understand a computer-mediated counter argument system, Huang et al [27] measured confidence level in individuals with confirmation bias, before and after an interruption by the system. In the fake news domain, Kim and Dennis [18] measure perceived believability of individuals with confirmation bias in a news article. They found confirmation bias towards a headline in an online Page 5894 poster had a significant positive effect on belief in the poster's topic.…”
Section: Confirmation Bias and Beliefmentioning
confidence: 99%
See 2 more Smart Citations
“…In their study to understand a computer-mediated counter argument system, Huang et al [27] measured confidence level in individuals with confirmation bias, before and after an interruption by the system. In the fake news domain, Kim and Dennis [18] measure perceived believability of individuals with confirmation bias in a news article. They found confirmation bias towards a headline in an online Page 5894 poster had a significant positive effect on belief in the poster's topic.…”
Section: Confirmation Bias and Beliefmentioning
confidence: 99%
“…Belief and confirmation bias are strongly tied together [26]. Several studies have shown the significant effect of confirmation bias on believability [18]. We control for confirmation bias in the proposed hypotheses from 1A to 1F.…”
Section: Theory Development and Model Conceptualization 31 What Makementioning
confidence: 99%
See 1 more Smart Citation
“…It's worth mentioning that we focus on those user-news interactions in which users agree with the news. For example, we only consider those users who share news pieces without comments, and these users share the same alignment of viewpoints with the news items [12]. We will introduce more details in Section 3.3.…”
Section: Problem Statementmentioning
confidence: 99%
“…Early fake news detection aims to give early alert of fake news, by only considering limited social context within a specific range of time delay of original news posted. Specifically, we change the delay time in [12,24,36,48,60,72,84,96] hours. From Figure 4, we can see that: 1) generally, the detection performance is getting better when the delay time increase for those methods using social context information, which indicates that more social engagements of users on social media provide more additional information for fake news detection; 2) The proposed TriFN consistently achieves best performances on both datasets for accuracy and F1, which demonstrate the importance of embedding user-news interactions to capture effective feature representations; and 3) Even in the very early stage after fake news has been published, TriFN can already achieve good performance.…”
Section: Early Fake News Detectionmentioning
confidence: 99%